Attachment styles of parents of adolescents and their parenting behavior - Kuterovac-Jagodić, Gordana; Keresteš, Gordana; Brković, Irma (2007)
The parent-child relationship and quality of parenting behavior have proven to be the most influential determinants of the child’ s development. While great effort has been spent studying the parenting behavior and consequences of parenting, much less attention has been devoted to studying determinants of parenting behavior. Along with the child characteristics, and contextual sources of stress and support, parenting is believed to be influenced by characteristics of the individual that are product of a person’ s developmental history (Belsky, 1984). The aim of the present study was to investigate how parental attachment history, defined as the relationship with their father and mother, and their current attachment style is associated with their parenting behavior. Participants were 812 pairs of parents and their school-age children (grades 5th to 8th) from different regions of Croatia. Parent attachment style was assessed by the mean of Adult Attachment Styles self-selection measure (Hazan & Shaver, 1987). Similar self-reported measure of retrospective parental caregiving styles was used (Hazan and Shaver, 1986). Parenting behavior was self-assessed as well as assessed by the child by the mean of Parental Behavior Questionnaire (Keresteš, Kuterovac Jagodić & Brković 2006) that measures parental acceptance and rejection, positive and negative discipline, monitoring and permissiveness. The findings indicate that parenting is related to parental attachment style, their recollections of caregiving styles of their parents, and their education, as well as by many complex interactions of those variables.
Projekt MZOS
ENG